European Landscape Convention - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
European Landscape Convention was adopted by Committee of Ministers of Council of Europe on 19 July 2000. It represents first the first international treaty wholly devoted to the protection, management of the European landscape. Its scope is very extensive. The Convention applies to the entire territory of the parties and relates to natural, peri / urban and urban areas whether on land, water or sea. It concerns remarkable landscapes, as well as everyday or degraded landscapes. Landscape means an area, as perceived by people, whose character is the result of the action and interaction of natural and/or human factors. It is dynamic category because landscape changes through time resulting from activities of human and natural factors. Landscape represents a whole consisting of natural and human elements. Public participation implies recognition of rights and responsibilities of populations to play active role in the processes of acquiring knowledge decision making and managing the quality of places where they live. It is not formal act but an integral part of management, protection and planning procedures. Public participation must be effective.